General Public Knowledge on the Halalness of Herbal Syrup in Yogyakarta Province, Indonesia - Utami, Nila Vidilia; Larasati, Savira Wahyu; Selalau, Waly Prakasa; Ghozali, Muhammad Thesa; Endarti, Dwi; Laksitorini, Marlyn Dian (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Background: Recently there is an increase concern regarding the halal certification of herbal medication. This is due to the potential use of alcohol in the extraction process as well as in the formulation of herbal syrup. Mueasurement of public knowledge regarding the halal aspect of herbal syrup containing alcohol has never been reported in Indonesia.Objective: The purposes of the study is to determine the level of public knowledge regarding halal aspect of herbal syrups in Indonesia, especially in Yogyakarta Province. Alcohol has been widely used in herbal products as a solvent for extraction. Trace of alcohol has been shown to be present in herbal syrup.Methods: 300 respondents from Yogyakarta Province, Indonesia from a variety of sociodemographic backgrounds were recruited. The study employed a modified paper-based questionnaire to collect the respondents' sociodemographic details and their level of awareness regarding the halalness of herbal syrups. The study employed descriptive statistics to examine sociodemographic variables and knowledge and used Chi-Square analysis to examine the correlation between demographic characteristics and knowledge.Results: The study suggests that the public has good knowledge regarding the halalness of herbal syrups (59.0%). However, around 41% of respondents still have low knowledge regarding the topic. The were a relationship between the age of the respondent and the level of knowledge (p<0.05). Respondents who are less than 45 years old tend to have a good knowledge of the halalness of herbal syrup while in the elderly population, more than 50% of the respondents showed a lack of knowledge on the topic studied.Conclusions: There are varying levels of understanding regarding the halalness of herbal syrups in the community. While the majority of responders have a good knowledge, a significant portion still do not fully grasp this concept. To increase public knowledge of the halal components in drugs, especially among the elderly, further strategies are needed.